The Effect of InternaI Parameter on the Dust Concentration in Broiler Houses - Elhussein, Hassan; Van den Weghe, Herman (agricultural engineering.eu, 1999)
The results of this study indicate that light has a significant effect on total dust concentration. The total dust concentration in the light period was two times more than in the dark period. The results show that the Ievel of total dust concentration varies significantly for difef rent days of measurement. It should be noted that, although the Ievels of dust concentration vary, there is no direct correlation between dust concentration and days.